The Induced Accumulation Of Gold In The Plants Brassica juncea, Berkheya coddii and Chicory - Lamb, A. E.; Anderson, C. W. N.; Haverkamp, R. G. (Massey University., 2001)
In this study the growth stubstrate of the plants Brassica juncea, Berkheya coddii and chicory were amended with thiocyanate and cyanide solutions to induce uptake and the gold concentrations in the different organs determined. Both species showed maximum uptake with cyanide amendment although thiocyanate also induced hyperaccumulation. Gold concentrations ranged from negligible in the leaves of B. coddii amended with thiocyanate, to 326 mg Au/kg dried biomass in the leaves of B. juncea amended with cyanide. The chemical additives KI, KBr, NaS2O3 were also used with the B. juncea and chicory. The results showed varying degrees of hyperaccumulation with all chemical treatments. Cyanide again gave the best results with 164 mg Au/kg dried biomass measured in the chicory plant. NaS2O3, KI and NaSCN gave maximum results of 51, 41 and 31 mg Au/kg dried biomass respectively. This technology has potential application in the economic recovery of metals.
Keywords: Hyperaccumulation; Gold; Phytoremediation